2017
DOI: 10.1002/cam4.1155
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year immune persistence and safety of the HPV‐16/18 AS04‐adjuvanted vaccine in females vaccinated at 15–55 years of age

Abstract: Women remain at risk of human papillomavirus (HPV) infection for most of their lives. The duration of protection against HPV‐16/18 from prophylactic vaccination remains unknown. We investigated the 10‐year immune response and long‐term safety profile of the HPV‐16/18 AS04‐adjuvanted vaccine (AS04‐HPV‐16/18 vaccine) in females aged between 15 and 55 years at first vaccination. Females who received primary vaccination with three doses of AS04‐HPV‐16/18 vaccine in the primary phase‐III study (NCT00196937) were in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 21 publications
3
52
1
Order By: Relevance
“…All participants remained seropositive to HPV16 following immunization with either vaccine and against HPV18 following immunization with Cervarix®, but seropositivity to HPV18 in the recipients who received the Gardasil® vaccine was lower than 100% after 7 years of follow up. These data are consistent with antibody binding data from 8-9 years of follow up of adolescents [10] or 16 -23 year old women [11] immunized with three doses of Gardasil®, a 10 year follow up study of 15 -25 year old women immunized with three doses of Cervarix® [12] and long term follow up (ca. 12 year) of women enrolled in the Finnish cohorts of the Phase 3 licensure trials of both Cervarix® and Gardasil® vaccines [13].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…All participants remained seropositive to HPV16 following immunization with either vaccine and against HPV18 following immunization with Cervarix®, but seropositivity to HPV18 in the recipients who received the Gardasil® vaccine was lower than 100% after 7 years of follow up. These data are consistent with antibody binding data from 8-9 years of follow up of adolescents [10] or 16 -23 year old women [11] immunized with three doses of Gardasil®, a 10 year follow up study of 15 -25 year old women immunized with three doses of Cervarix® [12] and long term follow up (ca. 12 year) of women enrolled in the Finnish cohorts of the Phase 3 licensure trials of both Cervarix® and Gardasil® vaccines [13].…”
Section: Discussionsupporting
confidence: 86%
“…A lower vaccine-type seropositivity rate for the neutralizing antibody response in Gardasil® vaccinees was also reported at 5 years in a head to head study of both vaccines in 18 -26 year old women [14]. Lower HPV18 seropositivity rates in Gardasil® vaccinees were evident in both the neutralizing and binding antibody responses reported here but these were higher than the rates reported from other studies [11,12,14] likely due to the younger age of the vaccine recipients in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…In a substudy of young men aged 16 to 26 years, the observed efficacy against anal disease was 75% for the vaccine types [6]. The clinical efficacy was demonstrated also in women aged from 15 to 45 years [7]; immunogenicity was evaluated in girls and boys from the age of 9 years and for adult women up to the age of 55 years [8]. Based on these data, all three vaccines are licensed by European Medicines Agency (EMA) for girls and boys from the age of 9 years without any upper age limit.…”
Section: Trial Resultsmentioning
confidence: 99%
“…For anti-HPV18, there were more seropositive females in the 15-to 25-year-old group (99.2%) than for the 26to 45-year-olds (93.7%) and 46-to 55-year-olds (83.8%) (90). In these studies, the anti-HPV16 and anti-HPV18 titers remained above natural infection levels in all of the age groups, and more interestingly, they were predicted to persist for more than 30 years after vaccination (91).…”
Section: Prophylactic Vaccinesmentioning
confidence: 63%